Annual Report on Exchange Arrangements and Exchange Restrictions 1986. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 1986)
This report describes developments in the international exchange rate and restrictive systems. The period covered by this report is 1985 and, for major developments, the first quarter of 1986. The report highlights that a salient feature of exchange rate developments in 1985 was the weakening of the U.S. dollar, following four consecutive years of appreciation. As a result, the currencies of most of the other major industrial countries appreciated against the U.S. dollar and in nominal effective terms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet